Effects of mirror therapy combined with theta burst stimulation on motor recovery of upper limbs after stroke: a randomized controlled study - Zhou, Jing; Chen, Mo; Dong, LuJie; Zheng, CaiXia; Xu, Jiang; Zhang, YangPu; Liu, YaLi (Frontiers in Neurology, 2025)
ObjectiveThis study aimed to explore the impacts of intermittent Theta burst stimulation (iTBS) and mirror image therapy (MT), both used separately and in combination with iTBS, on upper limb (UL) motor function, activities of daily living (ADL), and cortical excitability during the subacute phase of stroke.DesignRandomized controlled study.SettingInpatient rehabilitation centers of Tongji Hospital and Hubei Provincial Hospital of Integrated Chinese & Western Medicine.ParticipantsSeventy-one patients with upper limb (UL) disability.InterventionsPatients were randomly assigned to four groups. Three treatment groups received intermittent theta burst stimulation (iTBS), mirror therapy (MT), or a combination of both, in addition to routine rehabilitation. Therapy sessions were conducted five days per week for two weeks (10 working days).Main measuresThe assessments encompassed the National Institutes of Health Stroke Scale (NIHSS), upper limb Fugl-Meyer assessment (UL-FMA), modified Barthel index (MBI), Stroke-specific quality of life scale (SS-QOL), resting motor threshold (RMT), and motor evoked potential (MEP).ResultsThe combined treatment group showed significant improvements in UL-Fugl-Meyer Assessment (UL-FMA) scores compared with the control and MT groups (p < 0.05). Significant differences in Modified Barthel Index (MBI) and Stroke-Specific Quality of Life Scale (SS-QOL) scores were observed among the four groups (p < 0.05). On the contralesional side, the iTBS group demonstrated increased resting motor threshold (RMT), prolonged motor evoked potential (MEP) latency, and reduced MEP amplitude. In contrast, the MT group showed decreased RMT and MEP latency, along with increased MEP amplitude (p < 0.05).ConclusionThe addition of iTBS or combined therapy to conventional rehabilitation improved UL motor function and activities of daily living (ADL) in patients with stroke. The iTBS group exhibited inhibitory effects on contralesional hemisphere excitability, while the MT group showed facilitative effects. These excitability changes were less pronounced in the combined treatment group.Clinical trial registrationIdentifier ChiCTR1800015528.